Emulsified composition containing anionic modified cellulose fibers

JP2026167169APending Publication Date: 2026-10-14KAO CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025060601
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-04-01
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0007】 本発明によれば、アニオン変性セルロース繊維や有機化合物等を含有する乳化組成物を高温で保管した後であっても、優れた耐水性を発揮する膜を形成できる乳化組成物を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026167169000001
    Figure 2026167169000001
  • Figure 2026167169000002
    Figure 2026167169000002
  • Figure 2026167169000003
    Figure 2026167169000003
Patent Text Reader

Abstract

To provide an emulsified composition that can form a film exhibiting excellent water resistance even after being stored at high temperatures, such as when containing anionically modified cellulose fibers or organic compounds. [Solution] An emulsified composition containing the following components (A), (B), (C), and (D): Component (A): Anionically modified cellulose fiber with an average fiber length of 350 nm or less. Component (B): A silicone compound having a cationic functional group. Component (C): An oil (excluding those corresponding to component (B)). Component (D): Water.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to an emulsified composition containing anionically modified cellulose fibers. [Background technology]

[0002] Emulsified compositions using fine fibrous cellulose fibers (cellulose nanofibers) have been known for some time. Furthermore, Patent Document 1 discloses that a film with synovial properties can be obtained by applying an emulsified composition containing anionically modified cellulose fibers, amino-modified silicone, and an organic compound that is liquid at 25°C and 1 atm to a solid surface. Such films with synovial properties are beginning to be used as coating materials to prevent the adhesion of dirt. [Prior art documents] [Patent Documents]

[0003] [Patent Document 1] Japanese Patent Publication No. 2021-095557 [Overview of the project] [Problems that the invention aims to solve]

[0004] However, a new problem was discovered: when the above emulsified composition is stored at high temperatures, the water resistance of the dried film gradually deteriorates.

[0005] Accordingly, the present invention relates to providing an emulsified composition that can form a film exhibiting excellent water resistance even after being stored at high temperatures, when the emulsified composition contains anionically modified cellulose fibers, organic compounds, etc. [Means for solving the problem]

[0006] The present invention relates to the following [1] to [6]. [1] An emulsified composition containing the following components (A), (B), (C), and (D). (A) Anion-modified cellulose fibers having an average fiber length of 350 nm or less (B) A silicone compound having a cationic functional group (C) An oil agent (provided that those corresponding to the aforementioned component (B) are excluded) (D) Water [2] The emulsion composition according to the aforementioned [1], further comprising component (E). (E) A polymeric dispersant [3] The emulsion composition according to the aforementioned [1] or [2], wherein the content of component (A) is 3 parts by mass or more and 30 parts by mass or less relative to 100 parts by mass of component (B). [4] An emulsion composition obtained by blending the following component (A), component (B), component (C) and component (D). (A) Anion-modified cellulose fibers having an average fiber length of 350 nm or less (B) A silicone compound having a cationic functional group (C) An oil agent (provided that those corresponding to the aforementioned component (B) are excluded) (D) Water [5] A coating agent comprising the emulsion composition according to any one of the aforementioned [1] to [4]. [6] A film obtained by drying the emulsion composition according to any one of the aforementioned [1] to [4]. Effects of the Invention

[0007] According to the present invention, it is possible to provide an emulsion composition capable of forming a film that exhibits excellent water resistance even after the emulsion composition containing anion-modified cellulose fibers, organic compounds and the like has been stored at a high temperature. Modes for Carrying Out the Invention

[0008] The present inventors discovered the new problems as described above, and as a result of studies to solve such problems, focused on the average fiber length of anion-modified cellulose fibers, and conducted experiments by preparing anion-modified cellulose fibers having various average fiber lengths. As a result, an emulsified composition using shortened-fiber anion-modified cellulose fibers was prepared, the emulsified composition was stored under high-temperature conditions, and then a film was produced using the emulsified composition. It was surprisingly found that the water resistance of the film did not deteriorate, and the present invention was completed.

[0009] Although the mechanism by which such an effect is exhibited is not clear, it is presumed that the shortening of the cellulose fibers improves their mobility, lowers the viscosity, and allows a more uniform and highly stable structure to be formed during dry film formation.

[0010] <Emulsified Composition> The emulsified composition of the present invention contains the following component (A), component (B), component (C) and component (D).

[0011] <Component (A)> Component (A) is an anion-modified cellulose fiber having an average fiber length of 350 nm or less. The anion-modified cellulose fiber is a cellulose fiber that has been anion-modified so as to contain an anionic group in the cellulose fiber.

[0012] The average fiber length of the anion-modified cellulose fibers is 350 nm or less, preferably 330 nm or less, more preferably 310 nm or less, and still more preferably 300 nm or less, from the viewpoint of the water resistance of the film after storage under high-temperature conditions. On the other hand, from the viewpoint of emulsion stability, the average fiber length is preferably 50 nm or more, more preferably 100 nm or more, still more preferably 150 nm or more, and even more preferably 200 nm or more.

[0013] From the viewpoint of ease of handling, the average fiber diameter of the anion-modified cellulose fibers is preferably 0.1 nm or more, more preferably 1.0 nm or more, and even more preferably 2.0 nm or more. From the viewpoint of strength when a film is formed, it is preferably 200 nm or less, more preferably 100 nm or less, and even more preferably 50 nm or less. In this specification, anion-modified cellulose fibers with an average fiber diameter on the nm scale may be referred to as "finely milled anion-modified cellulose fibers." The average fiber diameter of the anion-modified cellulose fibers is measured by the method described in the examples below.

[0014] The average aspect ratio of the anion-modified cellulose fibers is preferably 5 or higher, more preferably 10 or higher, and even more preferably 20 or higher, from the viewpoint of emulsification stability, while from the viewpoint of water resistance of the film after storage under high-temperature conditions, it is preferably 300 or lower, more preferably 200 or lower, and even more preferably 100 or lower. The average aspect ratio of anionically modified cellulose fibers is calculated from the ratio of average fiber length to average fiber diameter.

[0015] Anion-modified cellulose fibers have a cellulose type I crystalline structure derived from the raw cellulose fibers. From the viewpoint of composition stability, the degree of crystallinity of the anion-modified cellulose fibers is preferably 10% or more, more preferably 15% or more, and even more preferably 20% or more. Furthermore, from the viewpoint of raw material availability, it is preferably 90% or less, more preferably 85% or less, even more preferably 80% or less, and even more preferably 75% or less.

[0016] In this specification, the degree of crystallinity of various cellulose fibers is the degree of cellulose type I crystallinity calculated from the diffraction intensity value by X-ray diffraction, and can be measured according to the method described in the examples below. Cellulose type I refers to the crystalline form of natural cellulose, and the degree of cellulose type I crystallinity means the proportion of the crystalline region in the total cellulose fiber. The presence or absence of a cellulose type I crystalline structure can be determined by the presence of a peak at 2θ = 22.6° in X-ray diffraction measurement.

[0017] Examples of anionic groups contained in anionic-modified cellulose fibers include carboxyl groups, sulfonic acid groups, and phosphate groups. From the viewpoint of bonding with component (B), the anionic group is preferably a carboxyl group. As anionically modified cellulose fibers, carboxyl-containing cellulose fibers, in which the anionic group is a carboxyl group, are preferred from the viewpoint of ease of preparation and mild reaction conditions.

[0018] Examples of counterions that pair with anionic groups in anionic-modified cellulose fibers include metal ions such as sodium ions, potassium ions, calcium ions, and aluminum ions, which are generated in the presence of alkali during manufacturing, and protons, which are generated by substituting these metal ions with acid.

[0019] The anionic group content in the anionic-modified cellulose fiber is preferably 0.1 mmol / g or more, more preferably 0.4 mmol / g or more, and even more preferably 1.0 mmol / g or more, from the viewpoint of bonding with component (B). Furthermore, from the viewpoint of improving handling, it is preferably 3.0 mmol / g or less, more preferably 2.0 mmol / g or less, and even more preferably 1.8 mmol / g or less. Note that "anionic group content" refers to the total amount of anionic groups in the cellulose constituting the cellulose fiber, and is specifically measured by the method described in the examples below.

[0020] [Method for producing anionically modified cellulose fibers] The anionically modified cellulose fibers used in the present invention are obtained by subjecting raw material cellulose fibers to an oxidation treatment or an anionic group addition treatment to introduce one or more anionic groups per glucose residue, thereby anionically modifying them. Shortened anionically modified cellulose fibers can be obtained by subjecting anionically modified cellulose fibers to a shortening treatment. Alternatively, they can be obtained by subjecting raw material cellulose fibers to a shortening treatment followed by an oxidation treatment or an anionic group addition treatment.

[0021] The cellulose fibers to be anion-modified, that is, the cellulose fibers used as raw materials for anion-modified cellulose fibers, are preferably natural cellulose fibers from an environmental standpoint. Examples include wood pulp such as coniferous pulp and hardwood pulp; cotton pulp such as cotton linters and cotton lint; non-wood pulp such as straw pulp and bagasse pulp; and bacterial cellulose. One of these can be used alone or in combination of two or more.

[0022] The average fiber diameter of the cellulose fibers used as raw materials is preferably 1 μm or more, and preferably 300 μm or less, from the viewpoint of handling ease and cost. Furthermore, the average fiber length of the cellulose fibers used as raw materials is preferably 100 μm or more, and preferably 5000 μm or less, from the viewpoint of availability and cost. From the viewpoint of dispersibility, it is preferable to use cellulose fibers in which the raw material cellulose fibers have been shortened by alkaline hydrolysis treatment, acid hydrolysis treatment, etc., and have an average fiber length of 1 μm or more and 1000 μm or less.

[0023] Examples of anionic groups that can be introduced include carboxyl groups, sulfonic acid groups, or phosphate groups.

[0024] (i) When introducing a carboxyl group as an anionic group into cellulose fibers Methods for introducing carboxyl groups into cellulose fibers include, for example, oxidizing the hydroxyl groups of cellulose to convert them into carboxyl groups, or reacting the hydroxyl groups of cellulose with one or more compounds selected from the group consisting of compounds having carboxyl groups, acid anhydrides of compounds having carboxyl groups, and derivatives thereof.

[0025] As a method for oxidizing the hydroxyl groups of the cellulose, for example, a method can be applied in which 2,2,6,6-tetramethyl-1-piperidine-N-oxyl (TEMPO) is used as a catalyst to react with an oxidizing agent such as sodium hypochlorite and a bromide such as sodium bromide to perform the oxidation treatment. More specifically, known methods, such as the method described in Japanese Patent Application Publication No. 2011-140632, can be referred to.

[0026] By oxidizing cellulose fibers using TEMPO as a catalyst, the hydroxymethyl group (-CH2OH) at the C6 position of the cellulose constituent unit is selectively converted to a carboxyl group. This method is particularly advantageous because it exhibits excellent selectivity for the hydroxyl group at the C6 position on the surface of the raw material cellulose fibers, and the reaction conditions are mild. Therefore, a preferred embodiment of the anionically modified cellulose fiber in the present invention is a cellulose fiber in which the C6 position of the cellulose constituent unit is a carboxyl group. In this specification, cellulose fibers obtained by oxidation of hydroxyl groups in cellulose constituent units are sometimes referred to as "oxidized cellulose fibers," and cellulose fibers obtained by oxidizing cellulose fibers using TEMPO as a catalyst, in which the C6 position of the cellulose constituent unit is a carboxyl group, are sometimes referred to as "TEMPO-oxidized cellulose fibers." Oxidized cellulose fibers, particularly TEMPO-oxidized cellulose fibers, are preferred because they are easier to prepare than other anionically modified cellulose fibers.

[0027] By further oxidation or reduction treatment of oxidized cellulose fibers, oxidized cellulose fibers from which the remaining aldehyde groups have been removed can be prepared.

[0028] (ii) When introducing a sulfonic acid group or a phosphate group as an anionic group into cellulose fibers Methods for introducing sulfonic acid groups as anionic groups into cellulose fibers include adding sulfuric acid to the cellulose fibers and heating them. Methods for introducing phosphate groups as anionic groups into cellulose fibers include mixing cellulose fibers in a dry or wet state with powder or aqueous solution of phosphate or a phosphate derivative, or adding an aqueous solution of phosphate or a phosphate derivative to a dispersion of cellulose fibers. When these methods are employed, generally, after mixing or adding powder or aqueous solution of phosphate or a phosphate derivative, dehydration and heat treatment are performed.

[0029] [Short fiber treatment] The short fiber treatment can be carried out by subjecting the target cellulose fibers to one or more treatment methods selected from the group consisting of (i) alkali treatment, (ii) acid treatment, (iii) heat treatment, ultraviolet treatment, electron beam treatment, mechanical treatment, and enzymatic treatment.

[0030] <Ingredient (B)> Component (B) is a silicone-based compound having a cationic functional group. Component (B) may be used alone or in combination of two or more types.

[0031] Examples of cationic functional groups in component (B) include amino groups, ammonium groups, and imidazolium groups, with amino groups being preferred from the viewpoint of availability. In this specification, an amino group means a monovalent functional group obtained by removing one hydrogen atom from ammonia, a primary amine, or a secondary amine.

[0032] The weight-average molecular weight of the silicone compound having a cationic functional group is preferably 2000 or more, more preferably 5000 or more, and even more preferably 8000 or more, from the viewpoint of film formation strength, and similarly, preferably 1,000,000 or less, more preferably 100,000 or less, and even more preferably 50,000 or less.

[0033] The silicone has a polysiloxane structure with siloxane bonds as the main chain, and may also contain alkylene groups. The polysiloxane structure may have substituents as described later.

[0034] [Substituent] Substituents include, for example, alkoxy groups having 1 to 6 carbon atoms such as methoxy, ethoxy, propoxy, isopropoxy, butoxy, isobutoxy, sec-butoxy, tert-butoxy, pentyloxy, isopentyloxy, and hexyloxy groups; methoxycarbonyl, ethoxycarbonyl, propoxycarbonyl, isopropoxycarbonyl, butoxycarbonyl, isobutoxycarbonyl, and sec-butoxycarbonyl Examples include alkoxy-carbonyl groups with 1 to 6 carbon atoms, such as carbonyl, tert-butoxycarbonyl, pentyloxycarbonyl, and isopentyloxycarbonyl groups; halogen atoms such as fluorine, chlorine, bromine, and iodine atoms; acyl groups with 1 to 6 carbon atoms, such as acetyl and propionyl groups; aralkyl groups; aralkyloxy groups; alkylamino groups with 1 to 6 carbon atoms; and dialkylamino groups with 1 to 6 carbon atoms in the alkyl group.

[0035] [Amino-modified silicone] Component (B) is more preferably a silicone having an amino group (hereinafter referred to as "amino-modified silicone") from the viewpoint of the stability of the composition.

[0036] As an amino-modified silicone, its kinematic viscosity at 25°C is 10 mmHg. 2 / s or more 20000mm 2 A concentration of less than or equal to / s is preferred. Furthermore, amino-modified silicones with an amino equivalent of 400 g / mol to 16000 g / mol are preferred.

[0037] The kinematic viscosity at 25°C can be determined using an Ostwald viscometer, and from the viewpoint of film formation strength, 20 mm is more preferable. 2 / s or more, more preferably 50mm 2 It is 10,000 mm or more, and more preferably from the standpoint of handling. 2 / s or less, more preferably 5000mm 2 It is less than or equal to / s.

[0038] Furthermore, the amino equivalent weight is preferably 400 g / mol or more, more preferably 600 g / mol or more, and even more preferably 800 g / mol or more from the viewpoint of strength during film formation, and is preferably 16000 g / mol or less, more preferably 14000 g / mol or less, and even more preferably 12000 g / mol or less from the viewpoint of ease of bonding to the anion-modified cellulose fibers. The amino equivalent weight refers to the molecular weight per nitrogen atom, and is determined by quantifying the amount of nitrogen atoms in the sample through elemental analysis and calculating the mass of the sample containing 1 mol of nitrogen atoms.

[0039] Specific examples of the amino-modified silicone include compounds represented by general formula (a1).

[0040]

Chemical Formula

[0041] [In the formula, R 1a represents a group selected from an alkyl group having 1 to 3 carbon atoms, a hydroxy group, an alkoxy group having 1 to 3 carbon atoms, or a hydrogen atom, and is preferably a methyl group or a hydroxy group from the viewpoint of water resistance. R 2a is a group selected from an alkyl group having 1 to 3 carbon atoms, a hydroxy group, an alkoxy group having 1 to 3 carbon atoms, or a hydrogen atom, and is preferably a methyl group or a hydroxy group from the same viewpoint. B represents a side chain having at least one amino group, and R 3a represents an alkyl group having 1 to 3 carbon atoms, a hydroxy group, an alkoxy group having 1 to 3 carbon atoms, or a hydrogen atom. x and y each represent an average degree of polymerization, x is an integer of 0 or more, y is an integer of 1 or more, and they are selected such that the kinematic viscosity at 25°C and the amino equivalent weight of the compound fall within the above ranges. Note that R 1a , R 2a , R 3a may each be the same or different, and a plurality of R 2a may be the same or different.]

[0042] In the compound of general formula (a1), from the viewpoint of emulsification stability, x is preferably a number between 10 and 10,000, more preferably a number between 20 and 5,000, and even more preferably a number between 30 and 3,000. Y is preferably a number between 1 and 1,000, more preferably a number between 1 and 500, and even more preferably a number between 1 and 200. From the viewpoint of film formation strength, the weight-average molecular weight of the compound of general formula (a1) is preferably 2,000 or more, more preferably 5,000 or more, and even more preferably 8,000 or more, and from the same viewpoint, preferably 1,000,000 or less, more preferably 1,000,000 or less, and even more preferably 50,000 or less.

[0043] In general formula (a1), the following can be considered as side chain B having an amino group. -C3H6-NH2 -C3H6-NH-C2H4-NH2 -C3H6-NH-[C2H4-NH] e -C2H4-NH2 -C3H6-NH(CH3) -C3H6-NH-C2H4-NH(CH3) -C3H6-NH-[C2H4-NH] f -C2H4-NH(CH3) -C3H6-N(CH3)2 -C3H6-N(CH3)-C2H4-N(CH3)2 -C3H6-N(CH3)-[C2H4-N(CH3)] g -C2H4-N(CH3)2 -C3H6-NH-cyclo-C5H 11 (Here, e, f, and g are numbers from 1 to 30.)

[0044] The amino-modified silicone used in the present invention can be produced, for example, by hydrolyzing an organoalkoxysilane represented by general formula (a2) with excess water to obtain a hydrolysate, and then heating the hydrolysate obtained from this hydrolysate with dimethylcyclopolysiloxane using a basic catalyst such as sodium hydroxide to 80-110°C to allow an equilibrium reaction to occur, and then neutralizing the basic catalyst with an acid when the reaction mixture reaches a desired viscosity (see Japanese Patent Publication No. 53-98499). H2N(CH2)2NH(CH2)3Si(CH3)(OCH3)2(a2)

[0045] Furthermore, the amino-modified silicone is preferably one or more selected from the group consisting of monoamino-modified silicone having one amino group in one of the side chains B and diamino-modified silicone having two amino groups in one of the side chains B, from the viewpoint of film formation strength, and more preferably one or more selected from the group consisting of compounds in which the amino-group-containing side chain B is represented by -C3H6-NH2 [hereinafter referred to as component (a1-1)] and compounds in which the amino-group-containing side chain B is represented by -C3H6-NH-C2H4-NH2 [hereinafter referred to as component (a1-2)].

[0046] In this invention, the amino-modified silicones are, in terms of performance, TSF4703 (kinematic viscosity: 1000, amino equivalent: 1600) and TSF4708 (kinematic viscosity: 1000, amino equivalent: 2800) from Momentive Performance Materials, and SS-3551 (kinematic viscosity: 1000, amino equivalent: 1700), FZ-3710 (kinematic viscosity: 1000, amino equivalent: 1700), SF8457C (kinematic viscosity: 1200, amino equivalent: 1800), SF8417 (kinematic viscosity: 1200, amino equivalent: 1700), SF8452C (kinematic viscosity: 600, amino equivalent: 6400), BY16-209 (kinematic viscosity: 500, amino equivalent: 1800), and BY16 -892 (kinematic viscosity: 1500, amino equivalent: 2000), BY16-898 (kinematic viscosity: 2000, amino equivalent: 2900), FZ-3760 (kinematic viscosity: 220, amino equivalent: 1600), BY16-213 (kinematic viscosity: 55, amino equivalent: 2700), KF-8002 (kinematic viscosity: 1100, amino equivalent: 170) manufactured by Shin-Etsu Chemical Co., Ltd. 0), KF-8004 (kinematic viscosity: 800, amino equivalent: 1500), KF-8005 (kinematic viscosity: 1200, amino equivalent: 11000), KF-867 (kinematic viscosity: 1300, amino equivalent: 1700), KF-864 (kinematic viscosity: 1700, amino equivalent: 3800), and KF-859 (kinematic viscosity: 60, amino equivalent: 6000) are preferred. (In parentheses, kinematic viscosity is measured at 25°C (unit: mm) 2 The value is expressed as ( / s), and the unit of amino equivalent is g / mol.

[0047] (a1-1) BY16-213 (kinematic viscosity: 55, amino equivalent: 2700) and BY16-853U (kinematic viscosity: 14, amino equivalent: 450) are more preferred as component (a1-1).

[0048] (a1-2) Component SF8417 (kinematic viscosity: 1200, amino equivalent: 1700), BY16-209 (kinematic viscosity: 500, amino equivalent: 1800), FZ-3760 (kinematic viscosity: 220, amino equivalent: 1600), SF8452C (kinematic viscosity: 600, amino equivalent: 6400), KF-8002 (kinematic viscosity: 1100, amino equivalent: 1700), SS-3551 (kinematic viscosity: 1000, amino equivalent: 1700), and FZ-3710 (kinematic viscosity: 1000, amino equivalent: 1700) are more preferred.

[0049] <Ingredient (C)> In this invention, component (C) is an oil. However, components corresponding to component (B) are excluded.

[0050] From the viewpoint of water resistance, the oil agent in the present invention can be one or more selected from the group consisting of higher alcohols, ester oils, hydrocarbon oils, silicone oils, ether oils, fats and oils, fluorinated inert liquids, and fatty acids. Preferably, one or more selected from the group consisting of ester oils, silicone oils, ether oils, fats and oils, and fluorinated inert liquids are preferred, more preferably one or more selected from the group consisting of silicone oils, ester oils, and ether oils are preferred, and silicone oil is even more preferred.

[0051] Examples of higher alcohols include 1-octanol, 2-octanol, 1-decanol, 2-decanol, oleyl alcohol, isostearyl alcohol, and behenyl alcohol, which are saturated or unsaturated linear or branched alkyl chains having 8 to 22 carbon atoms.

[0052] Examples of ester oils include monoester oils, diester oils, and triester oils. Specific examples include aliphatic or aromatic monocarboxylic or dicarboxylic acid esters having 2 to 18 carbon atoms, such as isopropyl myristate, octyldodecyl myristate, myristyl myristate, 2-hexyldecyl myristate, isopropyl palmitate, glyceryl tri-2-ethylhexanoate, and glyceryl triisostearate.

[0053] Examples of hydrocarbon oils include hydrocarbon oils that are liquid at 20°C, such as liquid paraffin, squalane, squalene, n-octane, n-heptane, cyclohexane, light isoparaffin, and liquid isoparaffin, and hydrocarbon oils that are solid or semi-solid at 20°C, such as petrolatum, ceresin, paraffin wax, microcrystalline wax, ozokerite, hydrogenated polyisobutene, polyethylene wax, and polyolefin wax.

[0054] Examples of silicone oils include siloxane compounds such as dimethylpolysiloxane, methylpolysiloxane, methylphenylpolysiloxane, octamethylcyclotetrasiloxane, and decamethylcyclopentasiloxane, as well as modified silicones such as phenyl-modified silicones, alkyl-modified silicones, polyether-modified silicones, and fluorine-modified silicones.

[0055] Examples of ether oils include alkyl-1,3-dimethylbutyl ether, ethylene glycol dioctyl ether, glycerol monooleyl ether, and dicaprylyl ether; one or more selected from these can be used.

[0056] Examples of oils and fats include vegetable oils such as soybean oil, coconut oil, linseed oil, cottonseed oil, rapeseed oil, and castor oil, as well as animal oils.

[0057] Examples of fluorinated inert liquids include hydrofluoroethers (HFE), perfluorocarbons (PFCs), and perfluoropolyethers (PFPEs). A commercially available example of a fluorinated inert liquid is Fluorinert (3M).

[0058] Fatty acids that are liquid at room temperature (25°C) are preferred, and examples include oleic acid, linoleic acid, and linolenic acid.

[0059] From the viewpoint of composition stability, component (C) preferably has an SP value of 10 or less, more preferably 9.5 or less, even more preferably 9.0 or less, and even more preferably 8.5 or less, and from the same viewpoint, preferably 6.0 or more, more preferably 6.5 or more. For example, an oil with an SP value of 10 or less, as described later, can be cited as a preferred example.

[0060] In this specification, SP value refers to the solubility parameter calculated by the Fedors method (unit: (cal / cm³) 3 ) 1 / 2 This is shown in references such as "SP Value Basics, Applications, and Calculation Methods" (Information Organization Co., Ltd., 2005) and "Polymer Handbook Third Edition" (A Wiley-Interscience publication, 1989).

[0061] Examples of oils with an SP value of 10 or less that are preferably used in the present invention include oleic acid (SP value: 9.2), D-limonene (SP value: 9.4), PEG400 (SP value: 9.4), dimethyl succinate (SP value: 9.9), neopentyl glycol dicaprate (SP value: 8.9), hexyl laurate (SP value: 8.6), isopropyl laurate (SP value: 8.5), isopropyl myristate (SP value: 8.5), isopropyl palmitate (SP value: 8.5), isopropyl oleate (SP value: 8.6), hexadecane (SP value: 8.0), olive oil (SP value: 9.3), jojoba oil (SP value: 8.6), squalane (SP value: 7.9), liquid paraffin (SP value: 7.9), and fluorinated inert liquids (e.g., fluorine-based inert liquids). Linart FC-40 (manufactured by 3M, SP value: 6.1), Florinart FC-43 (manufactured by 3M, SP value: 6.1), Florinart FC-72 (manufactured by 3M, SP value: 6.1), Florinart FC-770 (manufactured by 3M, SP value: 6.1)), silicone oil (for example, KF96-1cs (manufactured by Shin-Etsu Chemical Co., Ltd., SP value: 7.3), KF-96-10cs (manufactured by Shin-Etsu Chemical Co., Ltd.) Examples include KF-96-50cs (manufactured by Shin-Etsu Chemical Co., Ltd., SP value: 7.3), KF-96-100cs (manufactured by Shin-Etsu Chemical Co., Ltd., SP value: 7.3), KF-96-1000cs (manufactured by Shin-Etsu Chemical Co., Ltd., SP value: 7.3), KF-96-3000cs (manufactured by Shin-Etsu Chemical Co., Ltd., SP value: 7.3), KF-96H-10,000cs (manufactured by Shin-Etsu Chemical Co., Ltd., SP value: 7.3), etc. All of these oils are liquid at 25°C and 1 atm.

[0062] <Ingredient (D)> In this invention, component (D) is water. Water serves as a solvent during preparation and as one of the constituent components of the composition of this invention.

[0063] <Ingredient (E)> The emulsifying composition of the present invention may further contain a polymeric dispersant, component (E). Since polymeric dispersants have the effect of suppressing the aggregation of hydrophobic components in water, it is preferable to include or blend such components. Component (E) may be used alone or in combination of two or more types. Examples of polymeric dispersants include anionic polymeric dispersants. An anionic polymer dispersant is defined as "a polymer compound having an anionic group and whose countercation is one or more selected from the group consisting of ammonium ions and organic ammonium ions."

[0064] Such "polymeric compounds having an anionic group and whose countercation is one or more selected from the group consisting of ammonium ions and organic ammonium ions" may be formulated in the form of a salt of the "polymeric compound having an anionic functional group" and "one or more compounds selected from the group consisting of ammonia and organic amines," or the "polymeric compound having an anionic functional group" and "one or more compounds selected from the group consisting of ammonia and organic amines" may be formulated separately.

[0065] Examples of anionic functional groups in polymer compounds having such anionic functional groups include carboxyl groups, sulfonic acid groups, sulfate groups, phosphite groups, and phosphate groups. Among these, carboxyl groups are preferred from the viewpoint of ease of availability. The functional group equivalent in polymer compounds having such anionic functional groups is preferably 50 g / mol or more, more preferably 60 g / mol or more, from the viewpoint of the water resistance of the resulting film, and preferably 300 g / mol or less, more preferably 200 g / mol or less, from the viewpoint of the aggregation suppression effect. Here, "functional group equivalent" refers to the molecular weight per anionic functional group (i.e., molecular weight of the polymer compound having such anionic functional groups / number of anionic functional groups), and can be determined by quantifying the amount of anionic functional groups in the sample by neutralization titration and calculating the mass of the sample containing 1 mol of anionic functional groups.

[0066] Examples of polymer compounds having such anionic functional groups include polyacrylic acid, polymethacrylic acid, polymaleic acid copolymers, polyallyl sulfonic acid, and copolymers containing their constituent monomers. Among these, polyacrylic acid is preferred from the viewpoint of ease of availability. For example, ammonium polyacrylate is commercially available.

[0067] The weight-average molecular weight of the polymer compound having anionic functional groups is preferably 500 or more, more preferably 1000 or more, from the viewpoint of inhibiting aggregation, and similarly, preferably 200,000 or less, more preferably 100,000 or less, and even more preferably 50,000 or less.

[0068] The countercation here is preferably one or more selected from the group consisting of ammonium ions and organic ammonium ions. The organic ammonium ion may be any of primary, secondary, tertiary, or quaternary ammonium ions, all of which have an organic group. From the viewpoint of the water resistance of the resulting film, the number of carbon atoms in the organic group of the organic ammonium ion is preferably 15 or less, more preferably 10 or less, and even more preferably 6 or less. Organic ammonium ions are produced by the protonation of organic amines. Specific examples of organic amines that provide organic ammonium ions include methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, propylamine, ethylenediamine, triethanolamine, dimethylaminoethanol, aniline, pyrrolidine, and piperidine.

[0069] From the viewpoint of water resistance, the antication component is preferably one that volatilizes from the composition when the composition is dried to form a synovial surface film. From this viewpoint, ammonia (boiling point: -33°C), triethylamine (boiling point: 89°C), and dimethylaminoethanol (boiling point: 133°C) are more preferred as compounds that provide antications.

[0070] <Ingredients (G)> The emulsifying composition of the present invention may further contain component (G), which is a polymer compound not falling under (A), component (B), or component (C). Specifically, from the viewpoint of improving durability, component (G) is preferably one or more compounds selected from the group consisting of components (X) and (Y) below. The composition of the present invention may contain both component (X) and component (Y).

[0071] Component (X): A polymer compound having one or more groups selected from the group consisting of ester groups, amide groups, urethane groups, amino groups, ether groups, carbonate groups, and siloxane groups in its main chain.

[0072] Component (Y): A methacrylic or acrylic polymer compound having an ester group or amide group in its side chain.

[0073] The weight-average molecular weight of component (G) is preferably 1000 or more from the viewpoint of improving the durability of the film, and similarly, preferably 500,000 or less.

[0074] [Component (X)] Examples of components (X) having an ester group in the main chain include condensates of dicarboxylic acids such as adipic acid, sebacic acid, dodecanediic acid, phthalic acid, isophthalic acid, terephthalic acid, succinic acid, and alkenyl succinic acid with diols such as ethylene glycol, propylene glycol, and butanediol, or condensates of compounds such as glycolic acid and lactic acid that have both a hydroxyl group and a carboxyl group in one molecule.

[0075] Examples of components (X) having an amide group in the main chain include condensates of dicarboxylic acids such as adipic acid, sebacic acid, dodecanediic acid, phthalic acid, isophthalic acid, terephthalic acid, succinic acid, and alkenyl succinic acid with diamines such as aliphatic diamines such as ethylenediamine, hexamethylenediamine, and propylenediamine.

[0076] Examples of components (X) having a urethane group in the main chain include polymers of diisocyanates such as triresin diisocyanate, diphenyl isocyanate, xylylene diisocyanate, and hexamethylene diisocyanate with diols such as ethylene glycol, propylene glycol, and butanediol.

[0077] Examples of components (X) having an amino group in the main chain include polymers of alkylimines such as ethyleneimine, propyleneimine, butyleneimine, dimethylethyleneimine, pentyleneimine, and hexyleneimine.

[0078] Examples of components (X) having an ether group in the main chain include polymers of alkylene oxides such as ethylene oxide, propylene oxide, and butylene oxide, and polymers of formaldehyde.

[0079] Examples of components (X) having a carbonate group in the main chain include condensates of polyols such as 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxyphenyl)butane, and 1,1-bis(4-hydroxyphenyl)cyclohexane with phosgene.

[0080] Examples of components (X) having siloxane groups in the main chain include silicone elastomers and silicone acrylates.

[0081] [Component (Y)] Examples of methacrylic or acrylic polymers having ester or amide groups in their side chains (hereinafter also simply referred to as (meth)acrylic polymers) include polyalkyl (meth)acrylates such as polymethyl (meth)acrylate, polyethyl (meth)acrylate, and polybutyl (meth)acrylate; copolymers with acrylics such as styrene acrylic and urethane acrylic; and poly(meth)acrylamides such as poly(meth)acrylamide, polyN-methyl (meth)acrylamide, polyN,N-dimethyl (meth)acrylamide, and polyN-phenyl (meth)acrylamide.

[0082] In the present invention, from the viewpoint of improving the durability of the film, (X) a polymer compound having a urethane group in the main chain and / or (Y) a methacrylic or acrylic polymer compound having an ester group or amide group in the side chain are preferred. Other styrene polymers may also be used.

[0083] Component (G) is preferably formulated in the form of an emulsion or dispersion. When incorporating component (G), it is preferable to first prepare a mixture containing components (A) to (C), and then mix the mixture with component (G).

[0084] By incorporating component (G), it is possible to improve the adhesion between the dried film and the target substrate when applying the composition of the present invention to the target substrate and forming a dried film on the substrate. In particular, when applied to metal surfaces such as stainless steel, aluminum, and copper, plastic surfaces such as polyethylene, polypropylene, polycarbonate, and acrylic, or to dried coatings of acrylic, epoxy, silyl, and urethane paints, such as architectural paints, antifouling paints, anticorrosion paints, marine paints, automotive paints, industrial paints, snow protection paints, and household paints, the adhesion is significantly improved after drying. It is also possible to improve the viscosity of the composition by incorporating a polymer emulsion. By increasing the viscosity of the composition, dripping can be suppressed even when a thick coating is applied to a vertical surface. From the viewpoint of durability, the amount of component (G) is preferably 10 parts by mass or more, more preferably 50 parts by mass or more, and even more preferably 100 parts by mass or more, based on net component (G) per 100 parts by mass of anionic modified cellulose fiber. On the other hand, from the viewpoint of the synovial properties of the film, it is preferably 5000 parts by mass or less, more preferably 3000 parts by mass or less, and even more preferably 2000 parts by mass or less.

[0085] <Other ingredients> In addition to the components mentioned above, the emulsified composition of the present invention may contain, to the extent that it does not impair the effects of the present invention, antifouling agents, antibacterial compounds (e.g., organic synthetic antibacterial agents, natural antibacterial agents, and inorganic antibacterial agents), plasticizers, nucleating agents, fillers (inorganic fillers, organic fillers), hydrolysis inhibitors, flame retardants, antioxidants, hydrocarbon waxes and anionic surfactants as lubricants, ultraviolet absorbers, antistatic agents, antifogging agents, light stabilizers, pigments, foaming agents, surfactants; starches, polysaccharides such as alginic acid; natural proteins such as gelatin, glue, and casein; inorganic compounds such as tannins, zeolites, ceramics, and metal powders; fragrances; flow regulators; leveling agents; conductive agents; ultraviolet dispersants; deodorants, etc. Similarly, other polymer materials and other compositions may be added to the extent that they do not impair the effects of the present invention.

[0086] <Emulsified composition comprising components (A), (B), (C), and (D)> Another embodiment of the emulsified composition of the present invention is an emulsified composition comprising the above-mentioned components (A), (B), (C), and (D), and preferably further comprising component (E) and / or component (G) as needed.

[0087] <Properties of emulsified compositions> The emulsifying composition of the present invention contains the above-mentioned components (A), (B), (C), and (D) as essential components. The amount of each component used in the preparation of the emulsified composition of the present invention can be the same as the amount contained in the emulsified composition of the present invention.

[0088] The content of component (A) per 100 parts by mass of component (B) in the composition or during the preparation of the composition is preferably 3 parts by mass or more, more preferably 5 parts by mass or more, and even more preferably 10 parts by mass or more, from the viewpoint of stability of the composition, while from the viewpoint of handling, it is preferably 30 parts by mass or less, more preferably 25 parts by mass or less, and even more preferably 20 parts by mass or less.

[0089] The content of component (A) in the composition or during the preparation of the composition is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, and even more preferably 0.5% by mass or more, from the viewpoint of the stability of the composition, while from the viewpoint of handling, it is preferably 5% by mass or less, more preferably 3% by mass or less, even more preferably 2% by mass or less, even more preferably 1.5% by mass or less, and even more preferably 1.2% by mass or less.

[0090] The content of component (B) in the composition of the present invention or when preparing the composition of the present invention is preferably 10 parts by mass or more, more preferably 20 parts by mass or more, even more preferably 30 parts by mass or more, even more preferably 40 parts by mass or more, and even more preferably 50 parts by mass or more, per 100 parts by mass of component (C), from the viewpoint of the strength of the formed film and the stability of the composition, on the other hand, from the viewpoint of film-forming ability, it is preferably 100 parts by mass or less, more preferably 90 parts by mass or less, and even more preferably 80 parts by mass or less.

[0091] Furthermore, regarding the ratio of component (C) to component (A), from the viewpoint of composition stability, the content of component (A) is preferably 0.1 parts by mass or more, more preferably 1 part by mass or more, even more preferably 3 parts by mass or more, and even more preferably 8 parts by mass or more, per 100 parts by mass of component (C). On the other hand, from the viewpoint of handling, it is preferably 50 parts by mass or less, more preferably 30 parts by mass or less, and even more preferably 20 parts by mass or less.

[0092] The water content in the composition of the present invention or during the preparation of the composition of the present invention is preferably 40% by mass or more, more preferably 50% by mass or more, even more preferably 80% by mass or more, and preferably 95% by mass or less, more preferably 90% by mass or less.

[0093] In the present invention, when component (E) is included or blended, the content or blending amount of component (E) in the composition of the present invention or in the preparation of the composition of the present invention is preferably 0.01% by mass or more, more preferably 0.04% by mass or more, from the viewpoint of suppressing aggregation, while from the same viewpoint, it is preferably 0.5% by mass or less, more preferably 0.2% by mass or less, and even more preferably 0.15% by mass or less. When an anionic polymer dispersant is used as component (E), if a counter-cationic component is used or blended as a salt, the content of component (E) is the amount excluding the content of the counter-cationic component.

[0094] The composition of the present invention is an emulsified composition. The emulsified state is determined by visually observing the composition; if it is cloudy, it is considered to be in an emulsified state. The emulsified composition of the present invention may be either an O / W type emulsion or a W / O type emulsion, but an O / W type emulsion is preferred.

[0095] Applications of the emulsified composition of the present invention include, for example, coating agents that impart properties such as stain resistance, waterproofing, and prevention of adhesion of snow, bacteria, etc., to various surfaces located outdoors, such as road equipment such as signs, markers, traffic lights, and electronic display boards, as well as the bodies and glass surfaces of automobiles, airplanes, trains, ships, agricultural and industrial heavy machinery, motorcycles, etc., and coating agents for headlights, sensors, building roofs, exterior walls, windows, storage tanks, cooling towers, piping, outdoor units, carports, tents, offshore equipment, wharves, bridges, power plant equipment, power lines, etc., and solar panels, etc. Accordingly, one aspect of the present invention is a coating agent containing or comprising the emulsifying composition of the present invention described above.

[0096] The emulsifying composition of the present invention can be produced by mixing the aforementioned components. For the mixing process, a magnetic stirrer, mechanical stirrer, homomixer, vacuum emulsifier, low-pressure homogenizer, high-pressure homogenizer, grinder, cutter mill, ball mill, jet mill, short-screw extruder, twin-screw extruder, ultrasonic stirrer, household juicer mixer, etc. may be used. The mixing process may also be carried out by combining two or more operations.

[0097] The temperature and time for mixing each component are not particularly limited, but for example, the temperature range is preferably 5 to 50°C, and the time range is preferably 1 minute to 3 hours.

[0098] The preferred ranges for the content of each component and the ratios between components are the same as those preferred ranges in the compositions of the present invention described above.

[0099] By subjecting components or compositions containing anionically modified cellulose fibers to a micronization treatment at any stage of the composition's manufacturing process, micrometer-scale cellulose fibers can be reduced to a nanometer scale. Reducing the average fiber diameter of the anionically modified cellulose fibers to a nanometer scale improves the stability of the composition and the strength during film formation; therefore, it is preferable to carry out such a micronization treatment process.

[0100] For the micronization process, known dispersers are preferably used. For example, disintegrators, beaters, low-pressure homogenizers, high-pressure homogenizers, grinders, cutter mills, ball mills, jet mills, short-screw extruders, twin-screw extruders, ultrasonic stirrers, household juicer mixers, etc., can be used. Furthermore, the solid content in the material to be micronized is preferably 50% by mass or less. The operating conditions of the equipment during the micronization process can be appropriately set by those skilled in the art based on known operating conditions or the operating conditions described in the instruction manuals for each piece of equipment.

[0101] One aspect of the present invention is a film obtained by drying the emulsifying composition of the present invention described above. The film of the present invention can be manufactured by drying the emulsified composition of the present invention described above to form a film. For example, the composition of the present invention can be applied to a hard surface (e.g., a metal surface, a resin surface, a glass surface, a ceramic surface, etc.) and dried at room temperature and pressure, or by heating or reducing pressure as necessary, to form a film. In the membrane, the anionically modified cellulose fibers of component (A) and the silicone compound having cationic functional groups of component (B) form a salt.

[0102] The film exhibits synovial surface properties as described in the literature (Technology of Superhydrophobic, Superoleophobic, and Synovial Surfaces / Publisher: Hiroshi Motoki / Distributor: Science & Technology Co., Ltd. / Published January 28, 2016). In this specification, a film exhibiting such synovial surface properties (or simply "synovial properties") is also referred to as a "synovial surface film." Synovial surface properties can be measured, for example, by the method described in the "Slip Angle Measurement Test" in the examples below. A smaller slip angle value indicates higher synovial properties of the film. [Examples]

[0103] The present invention will be specifically described below with reference to examples. The following examples are merely illustrative of the present invention and do not imply any limitations. "Normal pressure" refers to a state without pressurization or depressurization, and "room temperature" refers to 25°C.

[0104] [Average fiber diameter and average fiber length of (shortened) anion-modified cellulose fibers] Deionized water was added to the cellulose fibers to be measured or a suspension containing the cellulose fibers to be measured to prepare a dispersion with a content of 0.01% by mass. This dispersion was measured using a wet dispersion type image analysis particle size distribution analyzer (Jusco International, IF-3200) under the following conditions: front lens: 2x, telecentric zoom lens: 1x, image resolution: 0.835 μm / pixel, syringe inner diameter: 6515 μm, spacer thickness: 500 μm, image recognition mode: ghost, threshold: 8, analysis sample volume: 1 mL, sampling: 15%. The length of the short axis and the length of the long axis were defined as the fiber diameter and major axis respectively when the cellulose fibers were approximated as rectangles, and these values ​​were measured for 100 cellulose fibers, and the average value was calculated.

[0105] [Average fiber diameter and average fiber length of cellulose fibers after micronization treatment] Deionized water was added to the cellulose fibers to be measured or a dispersion containing the cellulose fibers to be measured to prepare a dispersion with a cellulose fiber content of 1% by mass. After adjusting the pH to 9 with sodium hydroxide, the dispersion was treated five times at 150 MPa using a high-pressure homogenizer (NanoVeta L-ES, manufactured by Yoshida Machinery Industry Co., Ltd.). Deionized water was added to the dispersion so that the cellulose fiber content in the dispersion was 0.01% by mass. The dispersion was dropped onto mica, water droplets were removed with air, and the sample was dried. This sample was then measured in dynamic force mode using an atomic force microscope (AFM) (AFM-5100N, manufactured by Hitachi High-Tech Corporation; probe: SI-DF20P2, manufactured by Hitachi High-Tech Corporation). At that time, more than 100 cellulose fibers were extracted from the microscope image in which the cellulose fibers could be confirmed, and the average fiber diameter was calculated from the height of these fibers. The average fiber length was calculated from the distance in the direction of the fibers.

[0106] [Anionic group content of anionic-modified cellulose fibers] A 0.5 g dry weight of the cellulose fiber to be measured was placed in a beaker, and deionized water or a methanol / deionized water = 2 / 1 (volume ratio) mixed solvent was added to make a total volume of 55 mL. 5 mL of 0.01 M sodium chloride aqueous solution was then added to prepare a dispersion. The dispersion was stirred until the cellulose fiber was sufficiently dispersed. 0.1 M hydrochloric acid was added to the dispersion to adjust the pH to 2.5-3. Using an automatic titrator (Toa DKK Co., Ltd., AUT-701), 0.05 M sodium hydroxide aqueous solution was added dropwise to the dispersion with a waiting time of 60 seconds, and the conductivity and pH values ​​were measured every minute. Measurements were continued until the pH reached approximately 11, and a conductivity curve was obtained. From this conductivity curve, the amount of sodium hydroxide titration was determined, and the anionic group content of the cellulose fiber was calculated using the following formula. Anionic group content (mmol / g) = [Titration volume of sodium hydroxide aqueous solution (mL) × Concentration of sodium hydroxide aqueous solution (0.05M)] / [Mass of cellulose fiber to be measured (0.5g)]

[0107] [Confirmation of crystalline structure in various cellulose fibers] The crystalline structures of various cellulose materials, including cellulose raw materials and anion-modified cellulose fibers, were confirmed by measuring them using a diffractometer (MiniFlex II, Rigaku Corporation) under the following conditions. Measurement pellet preparation conditions: Pressure is applied to the target cellulose in the range of 10-20 MPa using a tablet molding machine, covering an area of ​​320 mm². 2 A smooth pellet with a thickness of 1 mm was prepared. X-ray diffraction analysis conditions: Step angle 0.01°, scan speed 10° / min, measurement range: diffraction angle 2θ = 5~40° X-ray source: Cu / Kα-radiation, tube voltage: 15kv, tube current: 30mA Peak splitting conditions: After removing background noise, a Gaussian function was fitted so that the error between 2θ = 13-23° was within 5%. The crystalline structures of various celluloses were confirmed by measuring them using the aforementioned diffractometer under the aforementioned conditions. The degree of crystallinity of the cellulose type I crystal structure was calculated using the area of ​​the X-ray diffraction peaks obtained by the aforementioned peak splitting, based on the following equation (A). Cellulose type I crystallinity (%) = [I cr / ( I cr +I am )] × 100 (A) [In the formula, I cr This is the area of ​​the diffraction peak at the lattice plane (002 plane) (diffraction angle 2θ = 22-23°) in X-ray diffraction, I am This indicates the area of ​​the diffraction peak in the amorphous region (diffraction angle 2θ = 18.5°).

[0108] [Anionic modified cellulose fiber 1] As the anionic modified cellulose fiber 1, TEMPO-oxidized cellulose fiber having the physical properties listed in Table 1 was used.

[0109] [Table 1]

[0110] Such anionically modified cellulose fibers can be prepared, for example, by the method described in the TEMPO oxidation treatment below.

[0111] In a 2L PP beaker equipped with a mechanical stirrer and stirring blades, weigh out 10g of bleached kraft pulp fiber from coniferous trees (as the raw material for natural cellulose fiber) and 990g of deionized water, and stir at 25°C and 100rpm for 30 minutes. Next, add 0.13g of TEMPO, 1.3g of sodium bromide, and 35.5g of 10.5% by mass sodium hypochlorite aqueous solution to 10g of pulp fiber in that order. Then, perform pH stat titration using an automatic titrator and add 0.5M sodium hydroxide aqueous solution dropwise to maintain the pH at 10.5. The reaction is carried out at 25°C for 120 minutes with a stirring speed of 100rpm.

[0112] Next, while stirring, 1M hydrochloric acid is added to adjust the pH of the suspension to 2. Then, the solids are filtered off by suction filtration. The process of dispersing the solids in deionized water and filtering them off by suction filtration is repeated until the conductivity of the filtrate is 200 μS / cm or less. The resulting solids are then dehydrated to obtain anionic modified cellulose fibers.

[0113] [Preparation of short-fiber anion-modified cellulose fibers] Anion-modified cellulose fiber 1 having the physical properties listed in Table 1 was subjected to a short-fiber treatment to obtain short-fiber anion-modified cellulose fibers having the physical properties listed in Table 2. These short-fiber anion-modified cellulose fibers were designated as component (A). Specifically, a cake of anion-modified cellulose fiber 1 was taken, and deionized water was added until the solid content concentration reached 5% by mass. The resulting mixture was stirred at the time and temperature shown in Table 2 to obtain an aqueous suspension of short-fiber anion-modified cellulose fibers. The obtained suspension was centrifuged using a high-speed refrigerated centrifuge (Koki Holdings Co., Ltd., CR21G III) at 25°C, 10000G, and 1 minute to obtain short-fiber anion-modified cellulose fibers having the physical properties shown in Table 2 as a precipitate.

[0114] [Table 2]

[0115] Preparation Example 1 [Preparation of Dispersion 1 of Micronized Anionic Modified Cellulose Fibers] 20.30 g (solid content 4.0 g) of the above-mentioned short-fiber anion-modified cellulose fiber 1 and 9.0 mL of 1 M ammonia water (9.0 mmol as ammonia) were measured into a beaker, and deionized water was added to make a total of 200 g. This liquid was subjected to a micronization treatment in one pass at 150 MPa using a high-pressure homogenizer (Yoshida Machinery Co., Ltd., NanoVeta L-ES) to obtain dispersion 1 of micronized anion-modified cellulose fibers as shown in Table 3. The physical properties of the micronized anion-modified cellulose fibers in the dispersion are shown in Table 3.

[0116] Preparation Examples 2-3 [Preparation of Micronized Anionic Modified Cellulose Fiber Dispersions 2-3] Except for using 4.0 g of either the short-fiber anion-modified cellulose fiber 2 or the anion-modified cellulose fiber 1 as the anion-modified cellulose fiber, the same procedure as described in Preparation Example 1 was performed to obtain the finely milled anion-modified cellulose fiber dispersions 2 and 3 shown in Table 3.

[0117] [Table 3]

[0118] Example 1 [Preparation of Emulsified Composition] In a beaker, 50.0 g of the dispersion of the above-mentioned finely pulverized anionic modified cellulose fiber 1 (solid content 2.0% by mass), 33 g of silicone oil 1, 6.0 g of amino-modified silicone 1, and 2.0 g of ammonium polyacrylate 1 (10% by mass aqueous solution) were mixed, and deionized water was added to make a total of 100 g. This mixture was subjected to 5 passes at 150 MPa using a high-pressure homogenizer (Yoshida Machinery Co., Ltd., NanoVeta L-ES) to prepare composition 1. The obtained composition 1 was a turbid liquid, and since oil droplets were observed to be dispersed in water using an optical microscope, it was determined to be an emulsion system.

[0119] Examples 2-3, Comparative Examples 1-2 [Preparation of Emulsified Compositions] Emulsified compositions were prepared using the same procedure as in Example 1, except that the components listed in Table 4 were used in the amounts listed in Table 4. The resulting compositions were cloudy liquids, and since oil droplets were observed to be dispersed in water under an optical microscope, they were all determined to be emulsions.

[0120] [Measurement of viscosity of composition] The viscosity of each composition prepared in the above examples and comparative examples was measured using an E-type viscometer (Anton Paar, MCR300) and a measuring jig: CP50-1 at a measurement temperature of 25°C, as follows: shear rate 0.1 s -1 from 7000s -1After measuring the viscosity of the composition while gradually increasing the shear rate up to 7000s, the viscosity was then reversed to 7000s. -1 from 0.1s -1 Viscosity was measured while gradually decreasing the shear rate up to 0.1s. Then, the shear rate was reduced again to 0.1s. -1 from 7000s -1 Viscosity was measured while gradually increasing the shear rate up to 1s in the final cycle. -1 The viscosity at [location] was defined as the viscosity of the composition.

[0121] [Membrane fabrication] Using the compositions prepared in the above examples and comparative examples, films were prepared as follows. For each example, 0.5 mL of the composition was spread onto a separate glass substrate (MATSUNAMI Micro Slide Glass S2112, 26 mm x 76 mm in size) and spread over the entire surface of the slide glass. Then, the film was prepared by drying at 1 atmosphere, 25°C, and approximately 40% RH for 24 hours.

[0122] [Evaluation of the water resistance of the film before storage] The membranes for each example, prepared as described above, were then prepared. The glass substrate with the film formed on it was immersed in a 300 mL beaker filled with water (approximately 23°C) and removed after 24 hours. The swelling rate of the film after 24 hours was calculated using the following formula A. The obtained swelling rate was defined as the "water resistance of the film before storage." A higher swelling rate indicates lower water resistance of the film.

[0123] <Formula A> Swelling rate [%] = [{[Mass after immersion] - [Mass of glass substrate before coating]} ÷ {[Mass before immersion] - [Mass of glass substrate before coating]} - 1] × 100

[0124] [Evaluation of the water resistance of the film after storage] The compositions for each example were left to stand in a constant temperature bath at 55°C for 45 days. Afterward, the films for each example were prepared using the same method as described in "Film Preparation" above, and the "Evaluation of Water Resistance of Films Before Storage" was performed. The water resistance of each membrane was evaluated using the same method as described in [reference]. The resulting swelling rate was defined as the "water resistance of the membrane after storage."

[0125] Table 4 shows the evaluation results for the composition, viscosity, and water resistance of each example. Note that the composition values ​​for each component in Table 4 are in mass%, and the amounts of each component are the net amounts of the component itself.

[0126] [Table 4]

[0127] From the above examples and comparative examples, it was found that the film obtained by applying and drying the emulsified composition of the present invention maintained its water resistance even after being stored at 55°C for 45 days (Examples 1-3). From this, it was found that the emulsified composition of the present invention can be used as a coating agent.

[0128] Manufacturing example [Manufacturing of anionic modified cellulose fiber 2] Even if anionically modified cellulose fiber 2, into which phosphoric acid has been introduced, is used instead of anionically modified cellulose fiber 1, into which carboxyl groups have been introduced, the same emulsified compositions as in Examples 1 to 3 can be obtained. Such anionically modified cellulose fiber 2 can be prepared by the following phosphorylation treatment. [Phosphorication treatment] To obtain chemically impregnated fibers, 100 parts by mass of bleached kraft pulp fibers from coniferous trees, which are used as the raw material for natural cellulose fibers, are impregnated with a mixed aqueous solution of ammonium dihydrogen phosphate and urea, and then pressed until the mixture contains 56 parts by mass of ammonium dihydrogen phosphate and 150 parts by mass of urea. The chemical-impregnated fibers are dried in a dryer at 105°C to evaporate the moisture. The fibers, from which the moisture has been evaporated, are heated in a forced-air dryer set to 140°C for 4 minutes. To 100 parts by mass of the obtained fibers, 10,000 parts by mass of deionized water are added, and the mixture is stirred to disperse the fibers. The solid components are then filtered off by suction filtration. To 100 parts by mass of solids in the filtered cake, 10,000 parts by mass of deionized water are added, and the mixture is stirred to disperse the fibers. The solids are then filtered off by suction filtration. To the resulting cake, 10,000 parts by mass of deionized water are added, and while stirring, a 1N sodium hydroxide aqueous solution is added dropwise to obtain a slurry with a pH of 12-13. Next, while stirring, 0.01M hydrochloric acid is added to adjust the pH of the suspension to 2. Then, the solid components are filtered off by suction filtration. The resulting cake is dispersed in deionized water, and the cake is filtered off by suction filtration. This process is repeated until the conductivity of the filtrate is 200 μS / cm or less. The resulting solid content is then dehydrated to obtain anionic modified cellulose fibers 2.

[0129] Details of the components used in the above examples are as follows: • Ammonia: Manufactured by Kanto Chemical Co., Ltd., 1 mol / L aqueous ammonia (1N) • Amino-modified silicone: SS-3551, manufactured by Dow-Toray (kinematic viscosity at 25°C: 1000 mmHg) 2 ( / s, amino equivalent: 1700 g / mol) • Ammonium polyacrylate: Manufactured by Toagosei Co., Ltd., Aron A30-SL • Silicone oil: Shin-Etsu Chemical Co., Ltd., KF-96-100cs (SP value: 7.3) [Industrial applicability]

[0130] The emulsified composition of the present invention can form a film with excellent water resistance even after high-temperature storage, and can therefore be used as a coating for applications where lubricating properties are desired in water or seawater, such as ship hulls and propellers, bridge frameworks, piping, quays, cooling towers, tank interiors, offshore equipment, observation equipment, and fishing nets.

Claims

1. An emulsified composition containing the following components (A), (B), (C), and (D). (A) Anionic modified cellulose fibers with an average fiber length of 350 nm or less (B) Silicone compounds having cationic functional groups (C) Oils (excluding those corresponding to component (B) above) (D) Water

2. The emulsified composition according to claim 1, further containing component (E). (E) Polymer dispersant

3. The emulsified composition according to claim 1, wherein the content of component (A) is 3 parts by mass or more and 30 parts by mass or less per 100 parts by mass of component (B).

4. An emulsified composition comprising the following components (A), (B), (C), and (D). (A) Anionic modified cellulose fibers with an average fiber length of 350 nm or less (B) Silicone compounds having cationic functional groups (C) Oils (excluding those corresponding to component (B) above) (D) Water

5. A coating agent containing the emulsifying composition according to any one of claims 1 to 4.

6. A film obtained by drying the emulsified composition according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Emulsion composition containing hydrophobic modified cellulose fiber

    JP2021095557A